Analisis Struktur Modal dalam Mengembangkan Usaha Dagang Surya Kota Gunungsitoli - Tiwi Elvis Zebua; Aferiaman Telaumbanua; Eliyunus Waruwu (Dinasti Review, 2024)
The success of a business is determined by a healthy capital structure that can support business operational activities. However, in the current era of modernization there are many businesses that are unable to develop their businesses and ultimately experience a decline in profits or income. This was experienced by the Surya Trading Business in Gunungsitoli City. Increased business competition makes it difficult for entrepreneurs to increase people's purchasing power, apart from that the lack of adequate infrastructure and complicated services also results in decreased public interest. Based on these problems, research was carried out which aimed to find out how the Solar Trading Business in Gunungsitoli City was developed through capital structure analysis. This research uses qualitative research methods with a descriptive approach. From the research results it is known that the difficulty of UD. Surya is growing because the level of capital owned by the business is not as large as the capital of other businesses that have just been established and operate in the same field. The lack of capital levels results in limited provision of resources, infrastructure, and minimal funding to expand business locations. The conclusion of this research is that the decline in profits or business income is because the business cannot develop due to the lack of capital sources owned by UD. Sun. So it is recommended to increase capital sources by utilizing assets, making external loans, business collaborations, and utilizing information technology.